Personal Data Protection Of Artificial Intelligence In The Public Interest - Clara Ignatia Tobing (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2025)
The rapid development of artificial intelligence has a major influence on society. Speculations and paradigms in society give rise to many pros and cons regarding artificial intelligence. The research is classified as normative juridical research, utilizing written materials as data sources. Qualitative research methods are employed to describe and analyze various phenomena and perspectives. The research relies on secondary data from library research, including official documents, research reports, and primary legal materials with authoritative significance. In Indonesia, the rules regarding artificial intelligence can only rely on Regulation No. 27 of 2022. Unfortunately, this is also happening globally. There is no official policy governing the use of artificial intelligence. However, Personal data breaches often due to artificial intelligence cannot rely solely on that regulation. Artificial intelligence does have many benefits and uses, but the disadvantages and problems caused by artificial intelligence cannot be underestimated. Official regulations regarding artificial intelligence are needed to be a solution in protecting personal data that is often harmed by artificial intelligence.